Inoculum production from pig slurry for potential use in agricultural biogas plants. (August 2022) - Marchetti, Rosa; Vasmara, Ciro; Orsi, Anna
Graphical abstract: Highlights: Adding specialized inocula to anaerobic digesters can improve biogas yields. A procedure for inoculum production is described, which uses pig slurry as the only raw material. The inoculum performance was compared with that of digestates from full-scale biogas plants. The inoculum specific methanogenic activity was 28% higher than that of digestates. The inoculum specific methane yield was 39% higher than that of digestates. Abstract: Biogas production may benefit from the use of specialized microbial consortia (inocula) to increase biogas yields in anaerobic digesters. For this study, a specialized inoculum was obtained from raw pig slurry by applying an innovative procedure. The aims of this research were: i) to compare the performance of this inoculum in the anaerobic digestion (AD) of four agricultural feedstocks with that of digestates commonly used for bioaugmentation of agricultural biogas plants; ii) to assess the duration of the methanogenic activity of this inoculum. The nutrient content of the residual liquid from inoculum production for its potential re-use as fertilizer was also assessed. Specific methanogenic activity and specific methane yield of the inoculum from pig slurry were higher (+28% and + 39% on average) than those of the two digestates. The inoculum successfully maintained its AD performance, almost unchanged, for a prolonged storage period (up to one year). The residual clarified liquid from inoculum preparation contains nutrients and mineral salts at very low concentrations. A possible way to recycle it could be fertigation. Inoculum production from pig slurry represents an additional possibility of valorisation of animal waste, from the storage tank to land spreading, in a context of biorefinery.